2017
DOI: 10.18632/oncotarget.16083
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of histological subtype in patients with metastatic bladder cancer

Abstract: We aim to evaluate the prognostic effect of the histological sub-type in patients with metastatic bladder cancer based on the Surveillance Epidemiology and End Results database. A total of 2634 eligible patients were included. The histological subtypes were: transitional cell carcinoma (TCC; 75.2%); adenocarcinoma (3.3%); squamous cell carcinoma (SQCC; 4.1%); and small cell carcinoma (4.3%). A significant association of adenocarcinoma with better survival outcomes (P < 0.015), and that of SQCC with worse outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 31 publications
4
24
0
Order By: Relevance
“… 34 Besides, Chen et al also suggested that the surgeries might improve patients’ OS outcomes. 9 Our study, for the first time, pointed out that patients with single metastatic site rather than multiple metastatic sites could benefit from RC, and that the RC was an independent prognostic predictor for metastatic BCa patients. Furthermore, this benefit could also be observed in patients with bone-only metastasis.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“… 34 Besides, Chen et al also suggested that the surgeries might improve patients’ OS outcomes. 9 Our study, for the first time, pointed out that patients with single metastatic site rather than multiple metastatic sites could benefit from RC, and that the RC was an independent prognostic predictor for metastatic BCa patients. Furthermore, this benefit could also be observed in patients with bone-only metastasis.…”
Section: Discussionmentioning
confidence: 58%
“…Our findings were unexpectedly contradictory to the results of the previous study, in which the multisite metastases were found to be able to independently predict worse OS and CSS. 9 The difference might arise from the different choices of the covariates in the Cox model, and further studies are needed to expound how the number of metastatic sites could affect the prognosis of patients with metastatic BCa. We specially did subgroup analyses based on patients with a single-site metastasis and found that patients with distant node-only and liver-only metastases had the best and the most unfavorable survival outcomes, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UBC has many histological types. Transitional Cell Carcinoma (TCC) is the most common histological type of primary UBC, which comprises more than 90% of all bladder tumors 6 . Except for TCC, this article also considers two other histological types which are squamous cell carcinoma (SCC) and Carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer is highly recurrent, metastatic and heterogenous, thereby resulting in poor prognosis [ 11 ]. It is postulated that bladder cancer stem cells are partly responsible for the clinical characteristics and complex biological behavior of bladder cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%